The Value of Local Wisdom of the Syawalan Tradition from a Social Studies Education Perspective - Lamiah, Jumaniyatu; Masrukhi, Masrukhi; Gunawan, Gunawan (Journal of Educational Social Studies, 2025)
This study aims to analyze the meaning of local wisdom values in the Syawalan tradition in Pedurungan Tengah Subdistrict, Pedurungan, Semarang, through a case study approach with qualitative methods. Syawalan tradition contains social, cultural, and religious dimensions that are in line with the objectives of Social Science Education (IPS): fostering understanding of social interaction, cultural diversity, and internalization of values in social life. Data were obtained through observation, in-depth interviews, and documentation. The data validity technique uses triangulation techniques, namely triangulation of methods and sources. The results showed that the Syawalan tradition functions as a means of inheriting the values of mutual cooperation, solidarity, respect for plurality, and strengthening local identity. In the Syawalan tradition, there are essential values for the formation of good citizenship. Thus, the integration of the Syawalan tradition into social studies education can be a pedagogical strategy to preserve local wisdom while actualizing the goals of national education in building a harmonious society, nation, and state.